Diversification Agriculture Project Alliance (DAPA) in Latin America - Oberthür, Thomas (Technical Centre for Agricultural and Rural Cooperation, 2006)
Thomas Oberthür explains how farmers, scientists, food processors and retailers are working together to improve the quality of agricultural products